Desenvolvimento de método exergoeconômico-ambiental: uso do biogás em motores de combustão interna - Vane, Lucas Fachini [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
In this thesis an econometric-environmental analysis methodology applied in generator-engines operating with biogas for the simultaneous production of electric energy and hot water is developed. The method developed has the objective of measuring the cost of CO2 emissions for this system, as well as to study its influence on the cost of operation by the technique of exergy cost of manufacture. The method is applied to internal combustion engines operating with biogas, with a production capacity of electric energy ranging from 4 kW to 2 MW, using or not the jacket water to produce hot water, depending on the type of engine cooling (air or water cooled). Two methods are applied for exergoeconomic-environmental analysis, the first one based on the method of cost distribution by the unitary exergy flows of the products and another based on the exergetic increments of the system components. It is concluded that both methods are satisfactory to evaluate the impact of the emission cost of pollutants and that the influence of this in the cost of exergético manufacture increases between 9,4% and 19,6% in relation to the traditional methods that do not consider the cost of pollution.

Neste trabalho de tese é desenvolvido metodologias de análise exergoeconômica-ambiental aplicado em motores-gerador operando com biogás para produção simultânea de energia elétrica e água quente. O método desenvolvido tem como objetivo mensurar o custo das emissões de CO2 para esse sistema, assim como estudar a sua influência no custo de operação pela técnica do custo de manufatura exergético. O método é aplicado a motores de combustão interna operando a biogás, com capacidade de produção de energia elétrica variando entre 4 kW a 2 MW, utilizando ou não a água da jaqueta para produção de água quente, dependendo do tipo de refrigeração do motos (a ar ou a água). Dois métodos são aplicados para análise exergoeconômica-ambiental, o primeiro baseado no método da distribuição de custo pelos fluxos exergéticos unitários dos produtos e outro baseado nos incrementos exergéticos dos componentes do sistema. Conclui-se que ambos os métodos são satisfatórios para avaliar o impacto do custo da emissão de poluentes e que a influência deste no custo de manufatura exergético incrementa entre 9,4 % e 19,6 % em relação aos métodos tradicionais que não consideram o custo da poluição ao meio ambiente.
Development of an exergo-economic-environmental method: use of biogas in internal combustion engines
Keywords: Biogás; Aspectos energéticos; Exergéticos e ecológicos; Análise exergoeconomica-ambiental; Biogas; Energy; Exergetic and ecologic aspects; Exergoeconomic-environmental analysis